The Development of Dose‐Dense Adjuvant Chemotherapy. Issue 1 (22nd December 2014) - Hudis, Clifford; Dang, Chau
Abstract Dose‐dense chemotherapy has made a significant contribution to the adjuvant treatment of breast cancer. One way of achieving dose‐density is through the use of sequential therapy with noncross resistant therapies to cause cell kill in tumors composed of heterogeneous cells. Another way to achieve this is to shorten the inter‐treatment interval to minimize the re‐growth of tumor cells, thus allowing for more effective cell killing. Several trials have tested this concept with the majority demonstrating improved efficacy with a dose‐density when compared with the traditional schedule. One such notable trial was CALGB 9741 that showed that when dose size and cycle numbers were kept constant, shortening the interval between each chemotherapy dose, with granulocyte‐colony stimulating factor support, significantly improved disease‐free and overall survival. This important and practice‐changing trial led to the wide adoption of dose‐dense chemotherapy and formed the basis of many subsequent studies, including allowing for the addition of biologic and targeted agents with excellent safety profile.